НӨКИС ҚАЛАСЫНЫҢ 90 ЖЫЛЛЫҚ ТАРИЙХЫНА БИР НӘЗЕР - Абдуллаева, Я.А. (FAN va JAMIYAT, 2022)
This article briefly presents the history of the city of Nukus from the time of its foundation as the capital to the present. Attention is paid to its special place in the development of the republic, its role in the socio-economic and socio-educational development of the state is shown by separate facts. In fact, during this time, the city of Nukus became the center of knowledge and culture